Dynamics of Accommodative Asthenopia in Patients with Visually Intense Work after LASIK with Different Degrees of Myopia - E. I. Belikova; D. V. Gatilov; I. G. Ovechkin; E. N. Eskina (Oftalʹmologiâ)
Purpose — to study the dynamics of accommodative asthenopia (AA) in patients with visually stressful labor (VLT) after laser keratomileusis in situ (LASIK) with different degrees of myopia. Patients and methods. There were 300 patients with VLT under supervision, divided into three groups of equal age and gender, corresponding to weak (up to 3.0 diopters, 100 patients, 200 eyes), medium (3.25–6.0 diopters, 100 patients, 200 eyes) and high (6.25–8.0 diopters, 100 patients, 200 eyes) degrees of myopia. All patients underwent objective accommodation using the Righton Speedy-I device (Japan) with further calculation of the coefficient of microfluctuations of the ciliary muscle of the eye (CMF). Diagnosis of the type of AA was carried out according to the following indicators: with CMF less than 53.0 rel. un. — asthenic form of accommodative asthenopia (AFAA); at CMF from 53.0 to 58.0 rel. un. — NORM; at CMF more than 58.0 rel. un. — habitual excess tension of accommodation (PINA). The survey was carried out before and three months after the operation. Statistical analysis of the results of the study was performed on the basis of the rate of occurrence (in % of the total number of eyes) of different dynamics (before-after surgery) AA (NORM-NORM; PINA-PINA; AFAA-AFAA; NORM-AFAA; NORM; PINA-AFAA; AFAA-NORM; AFAA-PINA). Results. The change in the form of AA varied from 2 % (APAA-PINA) to 18 % (PINANORM), averaged 15 % and was not statistically significant. The results obtained naturally reflect the state of AA as an adequate physiological response of the accommodative system of the eye to long-term, intense visual work with a fairly high level of responsibility for the result. Based on the above situation and the patient’s desire to maintain (in some cases even increase) the volume of daily visual load after the operation, it is unlikely to expect a significant improvement in the state of accommodation. Conclusion. LASIK with different degrees of myopia in patients with VLT has practically no effect on the dynamics of AA and requires a complex of therapeutic and restorative measures based on the development of methodological principles from the standpoint of a differentiated approach to the form of AA and the basic provisions of medical rehabilitaton.